Mr. Munday and the rustlers - Pryor, Bonnie; Manyum, Wallop (New York : Prentice Hall Books for Young Readers, 1987)
Mr. Munday, a bumbling mailman, outwits ornery rustlers when he and his cat take care of a farm.
School Library Journal
4.1
K-3
Keywords: Robbers and outlaws -- Fiction; Farms -- Fiction; Cats -- Fiction; Postal service -- Letter carriers -- Fiction; Robbers and outlaws -- Fiction; Farms -- Fiction; Cats -- Fiction; Postal service -- Fiction